1988
DOI: 10.3354/meps048069
|View full text |Cite
|
Sign up to set email alerts
|

Sediment rafting: a novel mechanism for the small-scale dispersal of intertidal estuarine meiofauna

Abstract: ABSTRACT. Epontic diatoms from intertidal sandy sediments produce considerable quantities of extracellular mucopolysaccharides that are used for locomotion, adhesion to sediment particles and as antidesiccants. These mucoid exopolymers dry out during low tide and cement sandgrains together thus stabilizing the surficial deposit. Under benign microclimatic conditions in Pauatahanui Inlet, New Zealand, these mucoid films with bound surface sediments peel off the substratum and float onto the surface of incoming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The joint occurrence of all identified harpacticoid species in both the water column above and in the superficial sediment layer of the intertidal sandflats may in part be an artefact of (1) the stronger sampling effort in the water column (>500 samples of seawater but only 50 sediment samples), and (2) may result from passive suspension of some of the rarer species by wave action and tidal currents or sediment rafting (Hicks, 1988). In any case, the species list is subject to seasonal change.…”
Section: Specific Composition Of Harpacticoid Swimmersmentioning
confidence: 99%
“…The joint occurrence of all identified harpacticoid species in both the water column above and in the superficial sediment layer of the intertidal sandflats may in part be an artefact of (1) the stronger sampling effort in the water column (>500 samples of seawater but only 50 sediment samples), and (2) may result from passive suspension of some of the rarer species by wave action and tidal currents or sediment rafting (Hicks, 1988). In any case, the species list is subject to seasonal change.…”
Section: Specific Composition Of Harpacticoid Swimmersmentioning
confidence: 99%
“…However there is evidence of exceptions to this pattern. Meiobenthic copepods have been shown to have a passive dispersal mechanism in low-energy intertidal areas through sediment rafting (Hicks 1988a). On a high-energy intertidal beach in Oregon (USA) copepods displayed a large amount of active behavior by positively responding to microbially-enriched sediment (Kern & Taghon 1986), as has also been observed in laboratory studies under conditions of no-flow (Decho & Fleeger 1988a).…”
Section: Introductionmentioning
confidence: 99%
“…In a n attempt to determine the swimming potential of this species, experiments using emergence traps showed that, unlike members of an adjacent seagrass copepod assemblage, P. megarostrum did not actively emerge from the sediment and undertake bouts of swimming activity during high tidal periods (Hicks 1986). Evidence from this and other studies (Hicks 1984(Hicks , 1988) strongly suggests that this species, in particular young stages of the population, has great fidelity to sediment particles.…”
Section: Introductionmentioning
confidence: 91%
“…P. megarostrum is, however, a moderately sized species that is more superficial in its occupancy of bottom deposits. It does not actively swim into emergence traps during high water (Hicks 1986), and in situ stereomicroscope observations (Hicks 1988) have revealed that the smallest individuals, nauplii and copepodites particularly, are more conspicuous on the sediment surface than are the large females that tend to live about 1 mm or so deeper. Thus smaller individuals are predisposed to passive resuspenslon during the flood and ebb of the high water phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation